2023
DOI: 10.3390/cancers15082266
|View full text |Cite
|
Sign up to set email alerts
|

Adult Patients with Cancer Have Impaired Humoral Responses to Complete and Booster COVID-19 Vaccination, Especially Those with Hematologic Cancer on Active Treatment: A Systematic Review and Meta-Analysis

Abstract: The exclusion of patients with cancer in clinical trials evaluating COVID-19 vaccine efficacy and safety, in combination with the high rate of severe infections, highlights the need for optimizing vaccination strategies. The aim of this study was to perform a systematic review and meta-analysis of the published available data from prospective and retrospective cohort studies that included patients with either solid or hematological malignancies according to the PRISMA Guidelines. A literature search was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 155 publications
0
1
0
Order By: Relevance
“…A review of 60 studies evaluating the COVID-19 vaccine efficacy in patients with either solid tumors or hematological malignances was conducted by Liatsou et al [ 70 ]. The findings regarding humoral response showed that after the third vaccine dose, the effect size of the seroconversion rate for patients undergoing active therapy was estimated at 0.63 (95%CI: 0.54–0.72) for hematological cancers and 0.88 (95% CI: 0.75–0.97) for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 60 studies evaluating the COVID-19 vaccine efficacy in patients with either solid tumors or hematological malignances was conducted by Liatsou et al [ 70 ]. The findings regarding humoral response showed that after the third vaccine dose, the effect size of the seroconversion rate for patients undergoing active therapy was estimated at 0.63 (95%CI: 0.54–0.72) for hematological cancers and 0.88 (95% CI: 0.75–0.97) for solid tumors.…”
Section: Discussionmentioning
confidence: 99%